Parameter Optimization via Cuckoo Optimization Algorithm of Fuzzy Controller for Liquid Level Control - Saeed Balochian; Eshagh Ebrahimi (Journal of Engineering)
Cuckoo optimization algorithm (COA) is one of the latest evolutionary algorithms. Finding the best optimal point, rapid convergence, and simplicity in determining algorithm parameters are some merits of COA. In this paper, COA is applied to tuning optimal fuzzy parameters for Sugeno-type fuzzy logic controllers (S-FLCs) which are used for liquid level control. A programmable logic controller (PLC) is used with fuzzy controller. For this purpose, a liquid level control set and PLC have been assembled together. MATLAB/Simulink program has been used to achieve the optimal parameters of the membership functions. The results show clearly that the optimized FLC using COA has better performance compared to manually adjustments of the system parameters for different datasets.